The Effectiveness of Acceptance and Commitment Therapy on Social Anxiety, Academic Performance, and Homesickness among International Students at Imam Khomeini International University - Keshavarz, Somayeh (Health Nexus, 2025)
The present study aimed to investigate the effectiveness of Acceptance and Commitment Therapy (ACT) in reducing social anxiety, improving academic performance, and alleviating homesickness among students. This research employed a quasi-experimental design with pre-test and post-test and a control group. The statistical population consisted of students at Imam Khomeini International University. Using purposive sampling, 30 students with high levels of social anxiety and homesickness were selected and randomly assigned to experimental and control groups. The experimental group received ACT-based intervention in eight 90-minute sessions, while the control group did not receive any intervention. The findings, analyzed using analysis of covariance, indicated that Acceptance and Commitment Therapy significantly reduced social anxiety and homesickness and improved the academic performance of students in the experimental group compared to the control group (p